Chebyshev wavelet finite difference method: a new approach for solving initial and boundary value problems of fractional order - Nasab, Aliasghar Kazemi; Kilicman, Adem; Atabakan, Zohreh Pashazadeh; Abbasbandy, Saeid (Hindawi Publishing Corporation, 2013)
A new method based on a hybrid of Chebyshev wavelets and finite difference methods is introduced for solving linear and nonlinear fractional differential equations. The useful properties of the Chebyshev wavelets and finite difference method are utilized to reduce the computation of the problem to a set of linear or nonlinear algebraic equations. This method can be considered as a nonuniform finite difference method. Some examples are given to verify and illustrate the efficiency and simplicity of the proposed method.